The riddle of the Sphinx: why sphingosine‐1‐phosphate may help define molecular mechanisms underlying risk stratification for serious COVID‐19 infections - Hugh Rosen; Michael B A Oldstone (EMBO Molecular Medicine)
Abstract The sphingosine‐1‐phosphate (S1P) is a lysophospholipid signaling molecule with important functions in many physiological and pathological conditions, including viral infection. In this issue of EMBO Molecular Medicine, Marfia et al present a risk stratification based on S1P serum level as a novel prognostic indicator for COVID‐19 severity.